A Study on Customer Satisfaction of Mobile Wallet Services Provided by Paytm - Saviour F (International Journal of Engineering and Management Research, 2019)
In today – world, smart phone has become an essential part of one’s daily life. Mobile users can nowadays use their Smartphones to make money transactions or payments by using applications installed in the phone. There are several mobile wallets which provide these services. Mobile wallets are digital versions of traditional wallets that someone would carry in their pocket. They offer payment services through which the individuals/business can receive /send money via mobile devices. The present paper throws light upon the customer satisfaction level towards the ewallet services provided by paytm. It focusses on the services provided by Paytm wallet and its satisfaction level.